Effect of microstructure and mechanical properties of Al/Mg dissimilar alloy with Pb interlayer by friction stir welding - Bofang Zhou; Haiao Feng; Zixuan Leng; Hongxia Zhang (Journal of Science: Advanced Materials and Devices)
Combining aluminum/magnesium(Al/Mg) dissimilar alloys has great potential for realizing automotive lightweighting. The microstructure and mechanical properties of Al/Mg dissimilar alloy with stir-pin rotation speed and thickness of the Pb foil intermediate layer by friction stir welding are investigated. The experimental results indicate that the ideal joints can be obtained with the stir-pin rotation speed of 800∼1100 rpm when the welding speed is 30 mm/min. The intermetallic compounds in the weld nugget zone are mainly composed of Mg17Al12 and Mg2Al3. The tensile strength of the joint increases first and then decreases with the increase of the stir-pin rotation speed, reaching a maximum of 168 MPa at 1000 rpm. By introducing Pb foil as an interlayer in the friction stir welding of Al/Mg dissimilar alloys, based on the optimum process parameters for joining Al/Mg without an interlayer, the thickness of the Pb foil interlayer was varied in the range of 0⁓0.2 mm. The intermetallic compounds in the weld nugget zone of the joint are mainly composed of Mg2Pb and Mg17Al12. The tensile strength of the joint initially increases and then decreases with the increase in the thickness of the Pb foil intermediate layer, reaching a maximum of 193 MPa at the thickness of 0.1 mm under the welding speed is 30 mm/min and the stir-pin rotation speed is 1000 rpm, which is 15% higher than the strength of Al/Mg joints without an interlayer, and accounts for 70% of the AZ31B base material strength.